The role of infrequent and extraordinary deep dives in leatherback turtles (Dermochelys coriacea) - Houghton, Jonathan D. R.; Doyle, Thomas K.; Davenport, John; Wilson, Rory P.; Hays, Graeme C. (Journal of Experimental Biology, 2008)
Infrequent and exceptional behaviours can provide insight into the ecology and physiology of a particular species. Here we examined extraordinarily deep (300–1250 m) and protracted (>1h) dives made by critically endangered leatherback turtles ( Dermochelys coriacea ) in the context of three previously suggested hypotheses: predator evasion, thermoregulation and exploration for gelatinous prey. Data were obtained via satellite relay data loggers attached to adult turtles at nesting beaches ( N =11) and temperate foraging grounds ( N =2), constituting a combined tracking period of 9.6 years ( N =26,146 dives) and spanning the entire North Atlantic Ocean. Of the dives, 99.6% ( N =26,051) were to depths <300 m with only 0.4% ( N =95) extending to greater depths (subsequently termed `deep dives'). Analysis suggested that deep dives: (1) were normally distributed around midday; (2) may exceed the inferred aerobic dive limit for the species; (3) displayed slow vertical descent rates and protracted durations; (4) were much deeper than the thermocline; and (5) occurred predominantly during transit, yet ceased once seasonal residence on foraging grounds began. These findings support the hypothesis that deep dives are periodically employed to survey the water column for diurnally descending gelatinous prey. If a suitable patch is encountered then the turtle may cease transit and remain within that area, waiting for prey to approach the surface at night. If unsuccessful, then migration may continue until a more suitable site is encountered. Additional studies using a meta-analytical approach are nonetheless recommended to further resolve this matter.